2004
DOI: 10.1111/j.1525-1594.2004.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Adsorbents Recirculating System Dialysis for Liver Insufficiency and Sepsis Following Right Ventricular Assist Device after Cardiac Surgery

Abstract: We report a case of right heart failure (RHF) and sepsis with liver insufficiency in a 70-year-old patient after coronary artery bypass graft surgery. Three hours after surgery the patient suddenly developed therapy refractory cardiac arrest caused by RHF. He had to have emergency surgery, under which the graft to the right coronary artery was revised and a right ventricular assist device was implanted. Heart function recovered and the assist device was explanted on day 1 after surgery. Thoracic closure was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A mortality range over 60% can be expected when the MOF state is reached (4,7). Some authors have communicated isolated reports of satisfactory responses to recirculating adsorbent albumin (molecular adsorbent recirculating system [MARS]) therapy in similar situations (12).…”
Section: Discussionmentioning
confidence: 99%
“…A mortality range over 60% can be expected when the MOF state is reached (4,7). Some authors have communicated isolated reports of satisfactory responses to recirculating adsorbent albumin (molecular adsorbent recirculating system [MARS]) therapy in similar situations (12).…”
Section: Discussionmentioning
confidence: 99%
“…Otrud Vargas Hein et al (83) of Humboldt‐University of Berlin (Berlin, Germany) reported a case of right heart failure (RHF) and sepsis with liver insufficiency in a 70‐year‐old patient after coronary artery bypass graft surgery. Heart function recovered and the right heart assist device was explanted on day 1 after surgery.…”
Section: Liver Supportmentioning
confidence: 99%